2015
DOI: 10.1111/iej.12426
|View full text |Cite
|
Sign up to set email alerts
|

Indirect cytocompatibility of a low‐concentration hydrogen peroxide bleaching gel to odontoblast‐like cells

Abstract: The 17.5% H2O2 applied to tooth specimens for 5 min caused no alteration in the odontoblast-like cells. When this gel was applied for 45 or 15 min, a slight cytotoxicity, associated with alterations in phenotypic markers, was observed. However, cells were able to recover their functions up to 21 days post-bleaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…, Soares et al . ). Lower H 2 O 2 concentrations strongly induced the expression of proteins associated with the mineralization process, whereas these proteins were adjusted according to the concentration of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 97%
“…, Soares et al . ). Lower H 2 O 2 concentrations strongly induced the expression of proteins associated with the mineralization process, whereas these proteins were adjusted according to the concentration of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 97%
“…, , Soares et al . ). Changes in the pulp tissue occur after bleaching, such as intense cell proliferation (Benetti et al .…”
Section: Introductionmentioning
confidence: 97%
“…10 Soares et al recently reported on low-concentration (17.5%) and short-duration applications and found significantly reduced cellular damage under in vitro conditions. [12][13][14] There is interest in RCTs to assess compounds with lower concentration that would comply with standards such as those of the European Community. The objective of this work is to show the effectiveness of a bleaching gel (6%) catalyzed by titanium dioxide nanoparticles and activated by hybrid light.…”
Section: Introductionmentioning
confidence: 99%